In situ Net Electricity Balance Analysis at Different Time Spans: Case of an Existing Residential Building in Tropical Climate - Pérez Rodríguez, Brunilda Elizabeth; Chung-Camargo, Katherine; Chen Austin, Miguel; Hung León, Patricia Simoy (LACCEI, 2024)
The global need for sustainable solutions underscores the importance of net-zero energy (NZEB) buildings that reduce energy consumption and greenhouse gas emissions. The implementation of NZEB varies worldwide due to climate and construction methods. Although the benefits are obvious, according to the literature, only a few tropical countries have established policies that support NZEBs. Promoting NZEBs requires policies that address social and financial aspects and real incentives and measurements. Therefore, the objective of the study is to analyze the net electricity balance at different time intervals through the in-situ measurements in an existing residential building in a tropical climate; the selected case study is in Panama City, Panama, a semi-autonomous family residence, which is connected to the national electricity grid and an on-site photovoltaic solar generation system. The data is collected through an Emporia measuring device, model VUE Gen 2, with a minimum granularity of one second. Consumption and generation data are analyzed to verify how achievable the NZEB concept is at different periods (annual, monthly, daily, and hourly). This is possible for the time intervals presented. The feasibility of achieving the net electricity balance to achieve NZEB for the tropical climate of Panama is evidenced.